A effect of rotation in an orthotropic elastic slab - Santra, Sutapa; Das, Nayon Chandra; Lahiri, Abhijit (Zielona Góra: Uniwersytet Zielonogórski)
The fundamental equations of the two dimensional generalized thermoelasticity (L-S model) with one relaxation time parameter in orthotropic elastic slab has been considered under effect of rotation. The normal mode analysis is used to the basic equations of motion and heat conduction equation. Finally, the resulting equations are written in the form of a vector-matrix differential equation which is then solved by the eigenvalue approach. The field variables in the space time domain are obtained numerically. The results corresponding to the cases of conventional thermoelasticity CTE), extended thermoelasticity (ETE) and temperature rate dependent thermoelasticity (TRDTE) are compared by means of graphs.
Keywords: Orthotropic elastic slab; normal mode analysis; effect of rotation